Recent progress in efficient organic two-photon dyes for fluorescence imaging and photodynamic therapy - Xu, Liang; Zhang, Junzheng; Yin, Lingfeng; Long, Xueting; Zhang, Wenying; Zhang, Qichun (Journal of materials chemistry. C, Materials for optical and electronic devices, 2020)
Two-photon excitation has important advantages over conventional one-photon excitation due to its charming advantages including longer-wavelength excitation, lower auto-fluorescence, higher 3D resolution and less photobleaching. These advantages have generated a strong demand for efficient two-photon dyes with high two-photon absorption cross-sections and fluorescence quantum yields. For this reason, the emerging structure-property correlations that can serve as guidelines for the enhancement of two-photon absorption cross-sections and fluorescence quantum yields are summarized in detail. In addition, the existing challenges as well as future perspectives are also discussed. The enhancement of two-photon absorption cross-section, fluorescence quantum yield and singlet oxygen generation efficiency for organic dyes and their applications in two-photon excited fluorescence imaging and photodynamic therapy are summarized.